Traditional procurement versus public-private partnership: A comparison of procurement modalities focusing on bundling contract effects - Hojun Lee; Kiwan Kim (Asian Development Bank (ADB), 2018)
This paper studies the optimal structure of procurement contracts between public and private sectors by mainly comparing two typical procurement types: traditional procurement and public-private partnership (PPP). We first set up a principal-agent model focusing on bundling effects of procurement based on Hart (2003), and Iossa and Martimort (2015) to see under which conditions PPP has advantages over traditional procurement and vice versa. Then, we consider if the Republic of Korea's PPP structure in practice is well designed to maximize efficiency regarding the theoretical model. By reviewing the data on major investors and equity transactions of the Republic of Korea's PPP projects, we show that the bundling effects of PPP contracts, which is one of the main sources of efficiency, is limited under the current economic and political environment and derive policy implications for developing countries implementing PPP projects in the region.
Keywords: H54; H81; 330; bundling contract; infrastructure; public-private partnership; traditional procurement